IMF Survey, Volume 35, Issue 08. (IMF Survey; IMF Survey ;, 2006)
Spring Meeting overview; IMFC communique; IMF medium-term strategy; Krueger to resign; World Economic Outlook; Sub-Saharan Africa outlook; Asia outlook; Western Hemisphere outlook; Dealing with scaled-up aid.